2017
DOI: 10.1016/j.jep.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A standardized methanol extract of Eclipta prostrata (L.) L. (Asteraceae) reduces bronchial hyperresponsiveness and production of Th2 cytokines in a murine model of asthma

Abstract: The results presented herein demonstrate for the first time the anti-inflammatory activity of E. prostrata in a murine model of asthma, thereby supporting the ethnopharmacological uses of the plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Only 1 reference presented a model of asthma as an allergic inflammatory condition, where the species Eclipta prostrata was decreased bronchial hyperresponsiveness [50].…”
Section: Comparison Between Methods Used For Pharmacological Evaluatimentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 reference presented a model of asthma as an allergic inflammatory condition, where the species Eclipta prostrata was decreased bronchial hyperresponsiveness [50].…”
Section: Comparison Between Methods Used For Pharmacological Evaluatimentioning
confidence: 99%
“…Carrageenan-induced paw edema [132] Croton oil-induced ear edema [132] Peritonitis induced by lipopolysaccharide [132] Pleurisy induced by carrageenan [89] Model of induced arthritis [65] Model of induced asthma [50] Induced mucositis [37] Wound healing assay [102] Formalin test (inflammatory phase) [93] Psoriasis treatment (clinical trial) [36] Percentage ( The search for more classic pharmaceutical forms, such as drug solutions, found ethanolic or aqueous extracts, among others, of Smallanthus sonchifolius for direct application as topical use, for example, in ear edema as described by Oliveira et al [88]. Among the assayed extracts, the extract obtained by rinsing the leaves with acetone presented the highest percentage of ear edema inhibition (44 %) when applied in mice induced by croton oil.…”
Section: In Vitromentioning
confidence: 99%
“…It is used in the treatment of spleen enlargements, uterine hemorrhages, skin diseases, scorpion bites and respiratory disorders (Pithayanukul et al 2004;Khare, 2007). This plant has been experimentally proven to possesses nephroprotective, cerebroprotective, hepato-protective, anti-cancer, anti-asthma, mosquito larvicidal and ovicidal properties, toxicity against hepatitis-C virus, hair growth promoting activity, immunemodulatory property, antioxidant, lipid lowering activity and anti-venom property (Dungca, 2016;Chaudhary et al 2011;de Freitas Morel et al 2017;Jayathirtha and Mishra, 2004;Datta et al 2009;Govindarajan and Karuppannan, 2011). Presence of wedelolactone, ecliptamines, taraxastane glycosides, polythienyl and other phytochemicals has been reported in this plant (Zhang et al 2010;Liu et al 2012;Han et al 2013).…”
Section: Introductionmentioning
confidence: 94%
“…These outcomes show that EP can enhance colitis manifestations through the adjustment of invulnerable capacity in intestinal epithelial cells and recommends that EP has the potential restorative impact to intestinal aggravation. [15] Morel LJF et alhave been reported Eclipta prostrata (L.) L. (Asteraceae) has been utilized in Brazilian customary prescription to treat asthma and other respiratory ailments. [16] Ding S et al have been reported Tobacco smoke is the main source of the improvement of different lung maladies including lung disease through activating oxidant push and provocative reactions which added to the sores of ordinary human bronchial epithelial (NHBE) cell.…”
Section: Anti Inflammatory Activitymentioning
confidence: 99%